2018
DOI: 10.1080/13803395.2018.1432571
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual variability in neurocognitive performance is associated with time-based prospective memory in older adults

Abstract: These results indicate that cognitive control, as indexed by IIV in neurocognitive performance, may play a role in naturalistic PM, as well as in highly strategic, but not automatic, laboratory-based PM among older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 58 publications
4
10
0
Order By: Relevance
“…For example, future work might examine patterns of intraindividual variability (i.e., a marker of cognitive control; Hultsch, MacDonald, & Dixon, 2002) in PM accuracy over time. Research shows that older adults, including PLWH, show higher intraindividual variability in cognitive performance cross-sectionally (e.g., Morgan et al, 2011), which is associated with lower time-based PM (Sullivan, Woods, Bucks, Loft, & Weinborn, 2018) and declines in medication adherence (e.g., Thaler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, future work might examine patterns of intraindividual variability (i.e., a marker of cognitive control; Hultsch, MacDonald, & Dixon, 2002) in PM accuracy over time. Research shows that older adults, including PLWH, show higher intraindividual variability in cognitive performance cross-sectionally (e.g., Morgan et al, 2011), which is associated with lower time-based PM (Sullivan, Woods, Bucks, Loft, & Weinborn, 2018) and declines in medication adherence (e.g., Thaler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…With regards to cognition, participants completed the Repeated Battery for the Assessment of Neuropsychological Status [RBANS, Sullivan et al (2018)] and they were all tested for ApoE status. Sampling preparation and storage details can be found in the EPAD lab manual (available online at http:// www.ep-ad.org).…”
Section: Epad Lcsmentioning
confidence: 99%
“…Higher IIV-dispersion has been linked to poorer microstructural integrity of white matter pathways in older adults (Halliday et al, 2019) and persons with mild TBI (Sorg et al, 2021), particularly the genu and the superior longitudinal fasciculus. Higher IIV-dispersion is also related to poorer global cognition (Morgan et al, 2011), executive dysfunction (Sullivan et al, 2018), and difficulties multitasking (Fellows & Schmitter-Edgecombe, 2015). Taken together, there is both a conceptual and empirical basis to suggest that IIV-dispersion may measure an aspect of cognition that is important to PM in PLWH.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies show that the addition of PM intention can increase IIV-inconsistency during the ongoing task (e.g., Ball & Brewer, 2018; Joly-Burra et al, 2018). Correlational studies suggest that higher IIV-inconsistency is independently associated with lower event-based PM accuracy for both focal (e.g., Haynes et al, 2018; Schmitter-Edgecombe et al, 2020) and nonfocal (e.g., Ihle et al, 2017; Sullivan et al, 2018) cues. One study reported that IIV-dispersion is also negatively associated with time-based PM; specifically, Sullivan et al (2018) demonstrated that higher variability in scores across the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS; Randolph et al, 1998) showed a small, but independent association with poorer time-based PM in the laboratory and in daily life among 194 older Australians.…”
Section: Introductionmentioning
confidence: 99%